Strategy for the Implementation of the Village Financial System Application Effectively and Efficiently - Hesti Irnanta; Nur Latifa Isnaini Putri (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2021)
This study aims to assess the performance of the village government from the use of the SISKEUDES (Village Financial System) application in improving the quality of financial accountability in the village of Tanjungsari, Umbulsari District, Jember Regency. This research uses qualitative methods using a descriptive approach. Data obtained from observations and interviews with informants, in this case the village government, from the village head, village secretary, finance officer, financial staff, and planning staff, directly from the results of the interview data reduction, data presentation and withdrawal were carried out. Conclusion.